Translating Laura E. Richards into Polish - Anna Maria Czernow; Aleksandra Wieczorkiewicz (European Journal of American Studies)
In the process of translating Laura E. Richards’s poems into Polish, we decided to use two approaches: translating “Eletelephony” collectively and “My Japanese Fan” independently.  In translating “Eletelephony” into Polish, we explain why and how we decided to stay faithful to the governing principle behind the poem rather than to its original word-play of ‘elephant’ and ‘telephone,’ which was impossible to maintain in Polish. The challenges we encountered while translating “My Japanese Fan” were different and concerned grammatical gender and the use of pronouns. Offering two translations to “My Japanese Fan,” we explain our different translation strategies—with Aleksandra opting for playing with words and meaning, and Anna choosing to emphasize rhythm and rhyme.